A comparative study of three methods for detecting Fasciola infections in Nigerian cattle (2008)
Qualitative examination of Fasciola gigantica eggs in faeces and bile were compared with the detection of precipitating antibodies in sera by agar gel precipitation test (AGPT) in 1000 cattle slaughtered at the Bodija municipal abattoir in Ibadan, Nigeria. Faecal and bile examination methods detected (196) 33.5% and (389) 38.9% of the animals as positive for fasciolosis, while (474) 47.4% were positive by AGPT. Both direct bile examination and faecal egg detection methods have high specificity and positive predictive value (100%) when compared with AGPT. However, lower values for sensitivity and negative predictive value were observed for both faecal egg examination (66.5% and 67.9% respectively) and bile examination (81.0% and 78.9% respectively). Fecal and bile examination failed to detect 33.5% and 19.0% of the cases detected by AGPT. The results of this study revealed that the AGPT could become a better test for the herd diagnosis of bovine fasciolosis for veterinarians and other investigators in Nigeria.